Correlation of palpation versus ultrasound-assisted approach for locating the level of lumbar puncture used for subarachnoid block in elective cesarean delivery - Tiwari, Arjun Prasad; Shrestha, Amir Babu; Pradhan, Ritu; Baral, Bidur Kumar; Gurung, Tara; Shrestha, Sangeeta (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To correlate the level of lumbar puncture used for subarachnoid block in parturient undergoing elective cesarean delivery between palpation and ultrasound method; and to find its accuracy. Methods: This is an observational study, conducted in 314 parturient undergoing elective caesarean delivery under spinal anesthesia over the period of three months at Paropakar Maternity and Women's Hospital Kathmandu. The interspinous space identified by palpation method on lateral position for subarachnoid block and later the site confirmed by ultrasound. Results: In this study, intervertebral space identified by palpation was matched in 38.1% (i.e. 107 in 281 patients) when assessed with ultrasound (USG). In 166 (59.1%) patients, skin puncture level was determined by palpation was found to be one intervertebral space cephalic. In eight (2.8%) patients, one intervertebral space caudal while assed with USG. The correlation between intervertebral space determined by palpation and by ultrasonography was poor (correlation coefficient r=0.288).The kappa was 0.293±0.015. Conclusions: The level of lumbar puncture used for subarachnoid block in elective cesarean delivery by palpation method is poorly correlated (38.1%) with ultrasonographic identification of corresponding interspinous level.